Kinetic behaviour of the roasting/selective reduction process with the use of a mixture of bituminous coal and fuel oil as the additive: Technical paper - Angulo-Palma, Hugo Javier; Saldana, Manuel; Legrá Legrá, Ángel; Lamorú Urgellés, Alisa; Hernández Pedrera, Carlos; Gallegos, Sandra; Galleguillos Madrid, Felipe M.; Salazar, Iván; Toro, Norman (HEMIJSKA INDUSTRIJA (Chemical Industry), 2025)
Lateritic ore is currently the main raw material that allows extraction of Ni by the Caron process. To date, the kinetic behaviour of the roasting/selective reduction process of lateritic nickeli¬ferous ores on a pilot scale is largely unknown. In the present study, the kinetic behaviour, the controlling stage and the mechanisms that describe this process with the use of a mixture of 2 wt.% bituminous coal and 1.25 wt.% fuel oil as a reducing additive were determined during the evaluation of the high and low thermal profiles, respectively. The phases of the reduced/leached minerals and the fed ore were analysed by X-ray powder diffraction. It was observed that the mixture used as a reducing additive guarantees an adequate trans¬for¬mation in both thermal profiles; the relationship between the residual Ni and residence time is described by a first-order reaction with the determination coefficients greater than 0.949. Although the influence of post-combustion air is not analysed, the controlling stage was diffusion through the ash layer with an activation energy of 14.4060 kJ mol-1. Thus, the most precise combination to describe the process is diffusion through the ash layer and the growth of the nuclei.